Analisis Kemometrik terhadap Sidik Jari Kromatografi Lapis Tipis dan Aktivitas Antioksidan Ekstrak n-heksana Piperaceae (Piper betle, Piper crocatum, Peperomia pellucida) - Miftachul Jannah; Elok Kamilah Hayati (Universitas Tidar, 2026)
The use of medicinal plants is increasing as knowledge about bioactive compounds, such as those found in betelplants. Differences between species in the same family (Piper betle L., Piper crocatum Ruiz & Pav, andPeperomia pellucida (L.) Kunth) require identification to avoid herbal medicine counterfeiting. Themetabolomic approach in this study, based on untargeted compounds, uses thin-layer chromatography todetermine the metabolite profiles of the three betel species. The TLC results were visualized using the ImageJapplication to obtain quantitative data. Data processing was continued using chemometric methods with PCAto group species and OPLS-DA to identify Rf values that might have antioxidant potential. The PCA results, withtwo main components totaling 94%, successfully grouped the three species of the family Piperaceae, indicatingdifferences in their respective metabolite profiles. The OPLS-DA results effectively separated the samples basedon antioxidant activity into two categories strong (Piper betle L.) and weak (Piper crocatum Ruiz & Pav andPeperomia pellucida (L.) Kunth), with Rf values of 7, 9, and 14 as the main contributors. Rf 9 was selected forfurther analysis using FTIR because it has the best VIP and p-value. These findings support the importance ofa metabolomic approach for quality control and authentication of medicinal raw materials. Keywords: betel leaf, thin layer chromatography, antioxidant, PCA, OPLS-DA